Vascular Effects of the Fetal Hemoglobin Inducer Agent 3-(1,3-Dioxoisoindolin-2-yl) Benzyl Nitrate - Terroni, Barbara [UNESP]; de Moraes, Luis Henrique Oliveira; Pavan, Aline Renata [UNESP]; Rodrigues, Gerson Jhonatan; Dos Santos, Jean Leandro [UNESP] (MDPI, 2022)
Vascular endothelium is a protective layer of cells lining the lumen of blood vessels that plays important roles by releasing factors responsible for controlling the vascular tone, regulating the expression of pro-inflammatory cytokines, and expressing adhesion molecules involved in vascular hemostasis. Imbalance of vascular properties leads to endothelial dysfunction (ED) and cardiovascular damage. Some diseases, such as sickle cell anemia, are characterized by ED with reduction in the levels of nitric oxide (NO). Previously, we have shown that the fetal hemoglobin inducer agent 3-(1,3-dioxoisoindolin-2-yl) benzyl nitrate (Lapdesf-4c) could act as NO donor, inhibiting platelet aggregation and reducing the inflammation associated with SCA. However, the vascular effect of this compound was not yet studied. Herein, we evaluated the effects of Lapdesf-4c in vascular reactivity experiments using aortic rings from male Wistar rats (300 g/90 days). We have found that Lapdesf-4c induced vasodilation in the presence (E+) or absence of endothelium (E−) with an average of EMax values of 101.8 ± 3.33% and 111.8 ± 3.21%. The mechanism of action was studied using 1H-[1,2,4]oxadiazolo[4,3-alpha]quinoxalin-1-one (ODQ), L-NG-nitroarginine methyl ester (L-NAME), and hydroxocobalamin. The EMax values for those pathways were hydroxocobalamin (30.6 ± 2.21%), ODQ (4.75 ± 0.51%), and L-NAME (109 ± 3.65), suggesting that Lapdesf-4c exhibits NO-dependent mechanisms. Lapdesf-4c was able to prevent angiotensin-induced ED after incubation of aorta rings for 1 h. We found based on the concentration–effect curve using acetylcholine (ACh) that pEC50 values for the control, Ang II, and combination of (Ang II + Lapdesf-4c) were 6.73, 6.46, and 7.15, respectively. In conclusion, Lapdesf-4c has emerged as a new drug candidate that can promote vasodilation and act as a protective agent against ED, being useful to prevent vascular damage.
Keywords: endothelial dysfunction; nitric oxide; nitric oxide donors; vascular reactivity